Perceived Informativeness of Viral Marketing Messages: A Case Study of Panjab University - Gulati, Neha; Guru, Pushpa; Goyal, Indu (Gyan Management Journal, 2018)
Aim: To explore the influence of Gender, Age and Education Stream ES) on the Perceived Informativeness of Viral Marketing Messages (PIVMMJ. The intent is to find prominent Jactor(s) that influence different modes a/Viral Marketing (VM). Methodoloyy: Non-Probability Quota Sampling has been used to gather data of 100 respondents of Panjab University, Chandigarh. To test the influence of Gender on PIVMM, Mann-Whitney U Test and mean values have been used. Kruskal-Wallis test has been applied to study whether there is an impact of Age and ES on PIVMM. Findin9s: Internet Biogs (!BJ has been perceived as the most informative mode. of VM. There is no influence of Gender and ES on PIVMM. The impactof Age on PIVMM has been established only for Email and not for other four modes. The respondents of all four ES perceive IB most informative for VM.